GAMBARAN FAKTOR KEKAMBUHAN PADA PASIEN SKIZOFRENIA DI RUMAH SAKIT JIWA ACEH - Fauziah Fauziah; Jubir Jubir; Ruslaili Ruslaili (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2020)
In Indonesia, the highest prevalence is in the Province of Bali with 11% per 1000 population suffering from schizophrenia, while Aceh is ranked the fourth highest in Indonesia in severe mental disorders (schizophrenia). Medical record data, patients treated at the Aceh Government Mental Hospital in 2019 amounted to 4241 patients. In 2020 the number of patients treated was 1053 patients. This study aims to determine the description of the recurrence factor in schizophrenia patients at the Aceh Government Mental Hospital. This study is descriptive, the population of recurrence patients is 187 patients. Sampling of this research is proportional stratified random sampling as many as 65 respondents. This research was carried out in the inpatient room of the Aceh Mental Hospital and was carried out from 30 June to 05 July 2020. Data collection was carried out by means of guided interviews using a questionnaire. The results showed that the patient's compliance variable taking medication was 61.5% less, family support in the less category was 53.8% and the environmental support around the less category was 56.9%. It is expected that respondents will be more motivated and obedient during the treatment period and seek alternative activities to avoid maladaptive attitudes and behavior, for families and communities the community should accept, understand and help patients and families in dealing with situations that occur in their environment, so that they feel accepted and appreciated, for the management of the Aceh Government Hospital to improve education about the importance of taking medicine and make information facilities for patients and families in the form of print media, for educational institutions it is expected to provide information for nursing education, especially psychiatric nursing about what factors influence and most influence on the recurrence of schizophrenic patients, and for further researchers it is recommended to conduct further research with a longer time and a larger sample size in order to obtain more significant results.Keywords: Relapse, schizophrenia